Associations between asthma, overweight and physical activity in children: a cross-sectional study. (December 2016) - Willeboordse, Maartje; van de Kant, Kim; van der Velden, Charlotte; van Schayck, Constant; Dompeling, Edward
Abstract Background Asthma and obesity are highly prevalent in children, and are interrelated resulting in a difficult-to-treat asthma-obesity phenotype. The exact underlying mechanisms of this phenotype remain unclear, but decreased physical activity (PA) could be an important lifestyle factor. We hypothesize that both asthma and overweight/obesity decrease PA levels and interact on PA levels in asthmatic children with overweight/obesity. Methods School-aged children (n = 122) were divided in 4 groups (healthy control, asthma, overweight/obesity and asthma, and overweight/obesity). Children were asked to perform lung function tests and wear an activity monitor for 7 days. PA was determined by: step count, active time, screen time, time spent in organized sports and active transport forms. We used multiple linear regression techniques to investigate whether asthma, body mass index-standard deviation score (BMI-SDS), or the interaction term asthma x BMI-SDS were associated with PA. Additionally, we tested if asthma features (including lung function and medication) were related to PA levels in asthmatic children. Results Asthma, BMI-SDS and the interaction between asthma x BMI-SDS were not related to any of the PA variables (p ≥ 0.05). None of the asthma features could predict PA levels (p ≥ 0.05). Less than 1 in 5 children reached the recommended daily step count guidelines of 12, 000 steps/day. Conclusion We found no significant associations between asthma, overweight and PA levels in school-aged children in this study. However, as PA levels were worryingly low, effective PA promotion in school-aged children is necessary.